A Case Report of Catatonia and Neuroleptic Malignant Syndrome With Multiple Treatment Modalities: Short Communication and Literature Review. Issue 43 (October 2015) - Chiou, Yu-Jie; Lee, Yu; Lin, Chin-Chuen; Huang, Tiao-Lai
Abstract : Abstract: We describe a case with complicated clinical presentations who was difficult to treat. We described the possible etiologies and differential diagnosis of neuroleptic malignant syndrome (NMS), catatonia, and infection, in details. This patient was also referred to neuro-intensive care unit for extensive workup and treatments by neurologist guidelines. In addition, we also used lorazepam–diazepam protocol and antipsychotics, but both failed to completely relieve her symptoms. She eventually responded to electroconvulsive therapy (ECT). A 60-year-old female patient with schizophrenia was diagnosed to suspected pneumonia, urinary tract infection, and retarded catatonia at first. The brain computed tomography revealed no significant finding. She developed NMS caused by the administration of low-dose quetiapine (200 mg) after carbamazepine was discontinued. The Francis–Yacoub NMS rating scale (F-Y scale) total score was 90. We utilized lorazepam–diazepam protocol and prescribed bromocriptine and amantadine, but NMS was not improved. Meanwhile, we arranged the brain magnetic resonance imaging to survey the physical problem, which revealed agenesis of septum pellucidum and dilated lateral ventricles. She was then transferred to the neuro-intensive care unit on the 15th hospital day for complete study. The results of cerebrospinal fluid study and electroencephalography were unremarkable. She was transferred back to psychiatric ward on the 21st hospital day with residual catatonic and parkinsonian symptoms of NMS, and the F-Y scale total score was 63. Finally, her residual catatonic condition that followed NMS got improved after 11 sessions of ECT. On the 47th hospital day, the F-Y scale total score was 9. This report underscores that the ECT is an effective treatment for a patient of NMS when other treatments have failed.